CURRENT STATUS AND PROSPECTS OF THE APPLICATION OF KEVLAR (ARAMID) FIBERS IN POLYMER COMPOSITES FOR 3D PRINTING - POLISHCHUK, ANDRII; LISEVYCH, SVITLANA; BONEK, MIROSLAW (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The relevance of the use of Kevlar ( aramid ) fibers in polymer composites for 3D printing technologies is due to the need to create high-strength, lightweight and impact-resistant structures that are able to operate under cyclic and dynamic loads. Given the rapid development of extrusion technologies for additive manufacturing (FFF/FDM), there is a growing need to use composite materials with increased performance characteristics that cannot be provided by traditional thermoplastics. Kevlar fibers are characterized by high specific strength, low density, heat resistance, fatigue resistance and the ability to effectively absorb impact energy. Therefore, they are considered one of the most promising reinforcing components in the structure of polymer composites for 3D printing. The article analyzes the current state of development and application of polymer composites reinforced with chopped and continuous Kevlar fibers, considers the features of the fiber-matrix interfacial interaction, technological compatibility with ABS, ASA, polyamides, technical thermoplastics and engineering polymer systems, and also analyzes the mechanical, tribological and operational characteristics of Kevlar composites. Special attention is paid to the consideration of commercial materials, laboratory research and the latest technological solutions in the field of FDM/FFF printing with aramid fiber reinforcement. It is shown that existing industrial filaments mostly contain short fibers, while the technologies for introducing continuous Kevlar threads remain limited. Promising development directions are summarized: the creation of hybrid composites, the use of coextrusion technologies, the development of pellet-based mixtures composites ) and optimization of fiber orientation structure to increase the strength of 3D printed parts.